Manufacturing of nanocomposites with engineering plastics - Mittal, Vikas (Woodhead Publishing, 2015)
Manufacturing of Nanocomposites with Engineering Plastics collates recent research findings on the manufacturing, properties, and applications of nanocomposites with engineering plastics in one comprehensive volume. The book specifically examines topics of engineering plastics, rheology, thermo-mechanical properties, wear, flame retardancy, modeling, filler surface modification, and more. It represents a ready reference for managers and scholars working in the areas of polymer and nanocomposite materials science, both in industry and academia, and provides introductory information for people new to the field.
Keywords: Nanocomposites (Materials); Nanostructured materials -- Design and construction.; Composite materials.; elektronické knihy; electronic books